Quorum sensing LuxS/autoinducer-2 inhibits Enterococcus faecalis biofilm formation ability - Yang,Yue (2018)
Abstract Objective: To investigate the relation between biofilm formation ability and quorum sensing gene LuxS/AI-2. Materials and Methods: Enterococcus faecalis (E. faecalis) standard strain ATCC 29212 was used in the study. Long flanking homology polymerase chain reaction method was used to build the LuxS gene knockout strain. Sequential culture turbidity measurement and CFU counting were used to assess the proliferation ability of E. faecalis after the depletion of LuxS. 96-well plate assay was used to quantify the biofilm formation ability; CLSM was used to observe the attached bacteria areas, while scanning electron microscopy (SEM) was performed to observe biofilm microstructure conditions. Results: LuxS gene knockout strains were successfully constructed and identified. The results showed that proliferation ability of E. faecalis was not affected by the depletion of the luxS gene, and the biofilm formation ability of ΔLuxS 29212 significantly decreased (P<0.05). Conclusions: Collectively, our studies provide the LuxS gene's key role in controlling biofilm formation of E. faecalis, which presented a negative regulation, and furthermore, providing us a possible way to conquer the persistent apical periodontitis.